PENGARUH TRUST DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP SHOPEE DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SINGAPERBANGSA KARAWANG - KUSNANTO, DANANG; OKTAVIANY, RISKA AYU; RAHMA, RIDA (Jurnal Ecoment Global, 2020)
As for the purpose, to obtain empirical evidence and find clarity phenomena and conclusions about The EffectÂ  of Trust and E-Service Quality to Buying Decision in Online Shop Shopee at Economy and Business Faculty University of Singaperbangsa Karawang. The study was conducted by using desciptive and verification methods, such as collecting, presenting, analyzing, and testing hypothesis, and made conclusions and suggestions. Sample were collected by using Stratified Random Sampling and Purposive sampling methods with a sample od 100 respondensfrom a population of 3.597 people. The data analysis technique was used Bar Scale Analysis technique and Path Analysis by using Method Succesive Interval, Microsoft Office Excel 2010, and SPSS. Based on the research result trust variable (X1) has a significant effect of buying decision (Y) with a percentage of 53,1%, which means that further increasing trust consumer will increase buying decisions to the product offered. E-service qualiy (X2) has a significant effect on buying decision (Y) with a persentage of 15,1%, which means that e-service quality effect the rentention of customers. There is a simultaneous effect of trust and e-service quality variables on buying decision by 68,2% and the remaining 31,8% is influenced by other variables not examined in this study.Keywords: Trust, E-Service Quality, Buying Decision